524. Understanding the Treatment of Carbapenem-Resistant Enterobacteriaceae (CRE) Infections in the United States (US): Insights from a Survey of Hospital-Based Pharmacists - Potoski, Brian (Open Forum Infect Dis, 2019)
BACKGROUND: New anti-CRE antibiotics (ceftazidime–avibactam, C-A; meropenem-vaborbactam, M-V; plazomicin, PLZ) are associated with improved outcomes and lower toxicity than polymixins (PMs; colistin; polymyxin B) in treating CRE infections. We previously demonstrated that ~40% (range: 28–71%) and ~23% (16–41%) of CRE infections in the United States were treated with PMs or new agents, respectively, as of 1/19. METHODS: To understand formulary status, availability and positioning of new anti-CRE agents and PMs, we surveyed hospital-based Society of ID Pharmacists (SIDP) members (11–12/18; Qualtrics). RESULTS: There were 218 respondents from 41 states. Mean CRE infections encountered were 2.7/mo (0–36). C-A, M-V, PLZ were formulary restricted or non-formulary but available at 84%, 68% and 31% of hospitals, respectively; agents were stocked at 80%, 37% and 4%. In 33% of instances, C-A was presented to P&T a second time prior to approval. In rank order, reasons for adding a new agent to formulary were improved outcomes/efficacy, safety/toxicity, and local stewardship (ASP) opinion. Ranked reasons for not adding a new agent were infrequency of CRE, cost, concern for misuse, and limited data. A new agent was positioned as first-line against CRE pneumonia (PNA), bacteremia (BSI), abdominal (IAI) and urinary infections by 87%, 90%, 83% and 56% of respondents [Table]. Smaller hospitals (stratified as ≤200, 201–400, >400 beds) were more likely to have not made a formulary decision or have new agents as no buy (P = 0.0005), and less likely to have a new agent stocked (P = 7e(-8)) or to position a new agent as first line against CRE PNA, BSI and IAI (P = 0.009). Similar associations were not evident by hospital type (academic, community teaching, or non-teaching). CONCLUSION: New agents are positioned as the first line against CRE PNA, BSI and IAI at most US hospitals with an SIDP member pharmacist, but they are still prescribed less against CRE infections than PMs nationally. Smaller hospitals are less likely to have mechanisms for using new agents or to position them as the first line. Discrepancies between positioning and use of new agents may reflect a bias in SIDP membership toward larger hospitals with ASP, lags between endorsing a first-line agent and incorporating it into care, and/or conservative ASP approval of agents in individual cases. [Image: see text] DISCLOSURES: All authors: No reported disclosures.